The Influence of Consumer Buying Behavior on Continuously Intention the Application of Online Food Delivery (OFD) in Indonesia - Perangin-Angin, Fini Anjela; Simanjuntak, Megawati; Taryana, Asep (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Online food delivery (OFD) is a necessity in today's society. Companies continuously offer innovation to gain consumer loyalty. Consumer loyalty is the highest achievement to which companies in the service sector aspire. However, the switch behavior exhibited by modern consumers compels companies to constantly update their offerings to meet user needs and desires. Purpose: This study aims to analyze the impact of promotion, price value, social influence, perceived usefulness, ease of use, customer experience, restaurant search, and variety of food choices on consumer purchasing behavior, and the influence of consumer purchasing behavior on intention to continue using in the OFD industry. Design/methodology/approach: This study uses a quantitative method supported by qualitative data involving 400 respondents who are users of the GoFood, GrabFood, and ShopeeFood applications. The questionnaire was distributed through social media. The analysis was carried out using SEM LISREL.Conclusion: These findings are valuable for companies in the OFD industry to understand which factors are highly valued by consumers, helping to foster high levels of loyalty to their applications.Originality/value (State of the art): Only a few articles compare these three popular OFD applications in Indonesia Keywords: continuance intention, loyalty, online food delivery (OFD), promotion, social influence